Combination DCV/SOF is Effective in Achieving Sustained Response in Patients with HCV GT-3 - Vinall, Maria (MD Conference Express, 2014)
Hepatitis C virus genotype (GT)-3 is common worldwide and is accompanied by a significant disease burden. Among patients with cirrhosis, it is associated with increased risk of fibrosis progression, steatosis, and hepatocellular carcinoma. The Phase III Daclatasvir and Sofosbuvir for Genotype 3 Chronic HCV [ALLY-3; NCT02032901] trial evaluated the efficacy and safety of daclatasvir plus sofosbuvir in patients chronically infected with GT-3.